التوظيف المستدام للذكاء الاصطناعي في التعليم التقني: تحليل واقعي لآليات تعظيم القيمة المضافة وتقويض المخاطر المهنية (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the current state of sustainable employment of artificial intelligence (AI) in technical education by examining mechanisms for maximizing added value and mitigating professional risks. The research adopted a descriptive‑analytical approach and utilized a questionnaire distributed to 114 faculty members at public technical colleges in the cities of Zliten, Misrata, and Al‑Khoms.The results revealed that the utilization of AI in technical education remains at a moderate and limited level, falling short of the desired sustainability and effectiveness, and that adoption alone does not guarantee the expected impact on added value. In contrast, findings indicated that sustainable employment mechanisms, particularly AI‑integrated educational content and performance assessment, demonstrated statistically significant effects in improving the quality of educational outputs. It was also observed that AI contributes at a moderate positive level to reducing errors and supporting professional decision‑making, while no statistically significant differences were found in participants’ opinions attributable to their demographic characteristics. The study further indicated that high‑level challenges—such as weak digital infrastructure, a shortage of qualified competencies, and the absence of clear policies—impede sustainable employment, despite growing recognition of the importance of this technology.Based on these findings, the study recommends establishing clear national visions, policies, and strategies for organizing and employing AI in technical education, enhancing digital and technical infrastructure, and designing specialized practical training programs. Additionally, it calls for integrating AI into curricula and educational content, developing intelligent assessment systems, strengthening professional risk management, and encouraging applied research and international partnerships to ensure effective and sustainable implementation.
Keywords: Sustainable Employment of Artificial Intelligence, Technical Education, Added Value, Occupational Risks, Employment Mechanisms